A systematic review of factors influencing the effective use of mHealth apps for self-care - Azhar F.A.B.; Dhillon J.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Digital libraries; Information science; Mobile telecommunication systems; Adoption; Factors; mHealth; Mobile health; Self-care; Health care